Children's emotions and quality of products in participatory game design. Issue 101 (May 2017) - Gennari, R.; Melonio, A.; Raccanello, D.; Brondino, M.; Dodero, G.; Pasini, M.; Torello, S.
Abstract: The paper presents an empirical study centred on a participatory game design activity with 8–10 years old primary-school children, split in different sessions. The study assesses how children perform in game design and whether they are engaged in design tasks. To this end, the study gathers data concerning the quality of children's game design products, regarded as indicators of children's performance in game design. It collects data concerning children's emotions, which are taken as indicators of their engagement in game design. The paper statistically analyses and discusses how emotions and quality of products evolve across the game design experience, and how emotions are related to children's quality of products. Results of this work can help researchers, educators and practitioners manage a complex design experience with and for children, and identify key emotions for promoting quality of design work. Highlights: The paper discusses children's performance and engagement in participatory game design. It presents a participatory game design study with 8–10 year olds. The study assesses children's emotions, for engagement, and product- quality, for performance. The study analyses their correlations, and interpret results with observation data. The paper concludes with implications of the study for participatory game design.